Extract of Morinda lucida leaf rescues hypoglycaemic and dyslipidaemic conditions in Plasmodium berghei-infected mice - Abdulkareem Adam Olaitan; Babamale Abdulkareem Olarewaju; Anifowoshe Abass Toba; Opeyemi Olufunke Adenike Opeyemi Olufunke Adenike; Oloriegbe Nusirat; Adamolekun Comfort; Adetula Samson; Ala Adeola Adefoluke (Bulletin of Natural Sciences Research, 2022)
Increasing drug resistance is a great threat to malaria control. Therefore, a continuous investigation into alternative therapy to mitigate malaria-associated damages is important. In this study, we investigated the anti-hypoglycaemic and anti-hyperlipidaemic effects of aqueous extract of Morinda lucida leaf in Plasmodium berghei-infected mice. Twenty-five mice were randomly grouped into five: Uninfected, infected-untreated, chloroquine (20 mg/kg, per oral), and extract-treated (400 mg/kg and 800 mg/kg, respectively, per oral) groups. Fasting blood glucose was measured before parasite inoculation and after the last treatment. Blood was collected for lipid profile assay at the end of the 4-day treatment. Our results revealed that both chloroquine and the extract lowered parasite growth (p <0.05), while chloroquine and 400 mg/kg of the extract improved blood glucose in Plasmodium berghei-infection. More so, all the treated groups showed attenuated Plasmodium berghei-induced dyslipidaemia, with 400 mg/kg of the extract exhibiting better efficacy. Therefore, this study suggests that Morinda lucida leaf extract can be harnessed as a therapeutic regimen for improved malaria treatments and associated complications. Further study is recommended to elucidate the mechanism of anti-hypoglycaemic and anti-hyperlipidaemic activities of the extract and the possible bioactive compound(s) involved.